Legal Analysis of Case Handling Against Children Who Commit Abuse - Pulungan, Nita Nilan Sry Rezki; Dinda Adistya Nugraha; Wessy Trisna; Mohammad Ghuffran; Ridho Mubarak (Mahadi: Indonesia Journal of Law, 2025)
This article aims to provide an overview of the justice system for juvenile offenders of violent crimes. Criminal acts are not just committed by grownups but the perpetrator can also be a child. Child are the golden generation for the nation and state, for that children need attention, protection and coaching to ensure their growth and development, mindset, mentality and behavior. Aggressive behavior in children often stems from children's habits in the use of mobile phones that contain video games that refer to violent games. The event that often occurs today is the crime of persecution where the perpetrator is a child. The factor of acts of abuse committed by children is an action taken by children to express their disappointment with the victim which results in physical violence which often results in injuries, disabilities, and even death. This study identifies the procedure for giving demands for cases of abuse committed by children. The prosecution carried out by the child prosecutor is first pre-prosecuted to the child offender, the child prosecutor can track the investigation's development ultimately, public prosecutor obtains an investigation file that has been first finished the investigator will order to subsequently make an indictment and then can be given to the court the process of resolving instances of child abuse indonesia's court system. Instances of child abuse in indonesia's court system. Juvenile justice can use restorative justice and diversion takes place on the basis of the idea that responses and responses to children's criminal behavior in terms of abuse will not be effective nothing community's and involvement of victims, perpetrators. If it turns out that these two methods cannot be carried out, then a trial in court is the last way and effort that must be taken as a last resort.